Gut Microbiota and Immune Modulatory Properties of Human Breast Milk Streptococcus salivarius and S. parasanguinis Strains - Li, Shuo; Li, Na; Wang, Chenwei; Zhao, Yi; Cao, Jie; Li, Xuejing; Zhang, Ziyi; Li, Yue; Yang, Xin; Wang, Xiaoxin; Che, Chuanyan; Zhao, Yufeng; et al. (Frontiers in Nutrition, 2022)
Human breast milk Streptococcus spp. are transferred to infant guts via breast feeding, but their effects on the gut microbiota and immunity remain unclear. In this study, we characterized gut microbiota and immune modulatory properties of human breast milk S. salivarius F286 and S. parasanguinis F278 that had been shown to be able to colonize gut. The two Streptococcus strains were orally administered to mouse pups individually at 1×10^7 cells/day from postnatal Days 1 to 21. At postnatal week 3 (the weaning period), S. salivarius F286 reduced the colonic microbiota α-diversity, increased 21 amplicon sequence variants (ASVs), including bacteria from Akkermansia, Intestinimonas, and Lachnospiraceae, and decreased 52 ASVs, including bacteria from Eubacterium, Bifidobacterium, Escherichia-Shigella, and Turicibacter; however, S. parasanguinis F278 didn’t change the colonic microbiota. Both Streptococcus strains reduced the ileal mRNA expression of cytokine/transcription factor representatives of T helper (Th) cells, including IFN-γ (Th1), Gata3 (Th2), and TGF-β (Treg) in 2-week-old suckling mice, and promoted the ileal expression of Foxp3 and TGF-β, which are representatives of anti-inflammatory Treg cells, in 3-week-old weaning mice. The two Streptococcus strains exhibited anti-inflammatory potential when incubated in vitro with human peripheral blood mononuclear cells and TNF-α-treated gut epithelial HT29 cells. In C. elegans, both strains activated immune response genes, which was associated with their lifespan-prolonging effects. Our results suggest that S. salivarius F286 and S. parasanguinis F278 may exert regulatory (anti-inflammatory) roles in gut immunity and S. salivarius F286 can modulate gut microbiota, and highlight the probiotic potential of milk S. salivarius and S. parasanguinis strains.